Refining malaria diagnosis in high-transmission areas: a dual-approach with rapid diagnostic tests (RDTs) and dbPCR-NALFIA - Diane Yirgnur Some; Francois Kiemde; Hermann Sorgho; Marc Christian Tahita; Antonia Windkouni Bere; Abdoulaye Ouedraogo; Souleymane Vivien Banao; Kouadjo Bagre; Gérémie Djiri; Georges Some; Toussaint Rouamba; Yeri Esther Hien; et al. (Malaria Journal)
Abstract Background Malaria rapid diagnostic tests (RDTs) are an essential tool in managing febrile illnesses in endemic settings. However, persisting parasite antigen after treatment or spontaneous remission, which can be detected by histidine-rich protein 2 (HRP2)-based RDT or Plasmodium lactate dehydrogenase (pLDH)-based RDTs, could lead to misdiagnosis. To overcome the latter, a diagnostic approach combining sequential interpretation of two-step malaria RDTs incorporating two parasite antigens detecting PfHRP2 and pLDH coupled with a direct-on-blood mini PCR-nucleic acid lateral flow immunoassay (dbPCR-NALFIA) has been evaluated. Methods Febrile patients visiting two rural health facilities in Burkina Faso were enrolled. For each participant, an HRP2-based RDT and blood slides for microscopy (gold standard) were performed. A capillary blood sample was also collected in an EDTA tube and transported to laboratory to perform the two-step malaria RDT detecting HRP2 and LDH, and dbPCR-NALFIA testing. Malaria diagnostic results were sequentially interpreted and reported as: (i) positive when pLDH line appears regardless of the HRP2 results (PfHRP2 + /pLDH + or PfHRP2-/pLDH +); (ii) negative when both lines are absent (PfHRP2-/pLDH-); and (iii) undetermined when only the HRP2 line appears (PfHRP2 + /pLDH-). Undetermined cases were subsequently confirmed by dbPCR-NALFIA test and reported as positive or negative. Malaria microscopy was used as reference test of conclusive diagnostic results (PfHRP2 + /pLDH + , PfHRP2-/pLDH + or PfHRP2-/pLDH-) and qPCR for undetermined cases (PfHRP2 + /pLDH-). Results Out of 438 blood samples analysed, 87.2% (382/438) of patients with conclusive sequential interpretation of HRP2 and pLDH did not need confirmative testing with dbPCR-NALFIA. The sensitivity and specificity of these conclusive results were 98.8% and 95.3%, respectively. Following confirmation of undetermined sequential interpretation with dbPCR-NALFIA, the sequential algorithm had a sensitivity of 97.9%, a specificity of 94.8%, a positive predictive value of 97.2%, and a negative predictive value of 96.1%. For single HRP2-based RDT, the sensitivity was 95.2%, the specificity 73.2%, the positive predictive value 85.1%, and the negative predictive value 90.4%. Conclusions The sequential algorithm of the two-step RDTs combined with dbPCR-NALFIA on inconclusive results enhances the diagnosis of malaria in febrile patients.